Cephalic Distocia - -, Dr. dr. I Ketut Edy Sudiarta, SpOG (Surabaya Biomedical Journal, 2025)
The normal birth process is determined by 3 main factors, namely maternal power, pelvic size and fetus. Normal delivery is vaginal delivery with a fetus in occiput posterior presentation that proceeds naturally without the help of tools. If there is no occiput posterior presentation, there is a possibility that labor will be obstructed even though the shape and extension of the baby are within normal limits. Thus, a careful examination must be carried out to determine the position of the head in the pelvic cavity. Here we will explain several head positions that often cause dystocia.